Purification, Characterization and Evaluation of the Antitumoral Activity of a Phospholipase A2 from the Snake Bothrops moojeni - Breno Emanuel Farias Frihling; Ana Paula de Araújo Boleti; Caio Fernando Ramalho de Oliveira; Simone Camargo Sanches; Pedro Henrique de Oliveira Cardoso; Newton Verbisck; Maria Lígia Rodrigues Macedo; Paula Helena Santa Rita; Cristiano Marcelo Espinola Carvalho; Ludovico Migliolo (Pharmaceuticals, 2022)
Nature presents a wide range of biomolecules with pharmacological potential, including venomous animal proteins. Among the protein components from snake venoms, phospholipases (PLA2) are of great importance for the development of new anticancer compounds. Thus, we aimed to evaluate the PLA2 anticancer properties from Bothrops moojeni venom. The crude venom was purified through three chromatographic steps, monitored by enzymatic activity and SDS-PAGE (12%). The purified PLA2 denominated BmPLA2 had its molecular mass and N-terminal sequence identified by mass spectrometry and Edman degradation, respectively. BmPLA2 was assayed against human epithelial colorectal adenocarcinoma cells (Caco-2), human rhabdomyosarcoma cells (RD) and mucoepidermoid carcinoma of the lung (NCI-H292), using human fibroblast cells (MRC-5) and microglia cells (BV-2) as a cytotoxicity control. BmPLA2 presented 13,836 Da and a 24 amino acid-residue homologue with snake PLA2, which showed a 90% similarity with other Bothrops moojeni PLA2. BmPLA2 displayed an IC50 of 0.6 µM against Caco-2, and demonstrated a selectivity index of 1.85 (compared to MRC-5) and 6.33 (compared to BV-2), supporting its selectivity for cancer cells. In conclusion, we describe a new acidic phospholipase, which showed antitumor activity and is a potential candidate in the development of new biotechnological tools.